AN INVESTIGATION INTO HUMAN RESOURCE MANAGEMENT IN TEN SELECTED INTERNATIONAL SCHOOLS IN THE COLOMBO DISTRICT - PERERA, G.P.K. (My University, 2006)
The problem of the study was to investigate human resource management in international schools. This study was limited to ten international schools in the Colombo District. Descriptive research approach was used in this study. The objectives of the study were, 1. To identify the human resources in international schools and to highlight the significance of Human Resource Management. 2. To study the present situation of the Human Resource Management (HRM) in international schools. 3. To examine the extent of contribution the management of human resource has towards the achievement of school effectiveness. 4. To examine the ways and means of developing Human Resource Management in schools. The study had been conducted on a purposive sample of ten international schools in the Colombo District. The sample included ten school principals, fifty teachers, fifty students and fifty parents of students in international schools. Data were collected through questionnaires and interviews. The school principals were administered a questionnaire and interviewed. The teachers, students and parents were given questionnaires and the questionnaires given to parents and students included an attitude scale. The data collected were subjected to analysis according descriptive research approach, in terms of percentages, graphs, tables and criteria used in evaluating school effectiveness.